Factores asociados a la morbilidad materna extrema en pacientes del Hospital Apoyo Iquitos, año 2022 - Reátegui Valverde, María Fernanda (2024)
This research project focuses on extreme maternal morbidity, which includes serious clinical complications that compromise the vital integrity of women during gestation, delivery and the 42 days following delivery. Given the high prevalence of maternal mortality cases in our region, an observational, descriptive and cross sectional study will be carried out. The main objective is to analyze the factors linked to this extreme morbidity in pregnant patients attended at the Hospital Iquitos “Cesar Garayar García” during the year 2022. The study explores the relationship between sociodemographic variables such as age, origin, education, marital status and occupation, as well as maternal clinical characteristics such as prenatal control, number of pregnancies, previous deliveries and type of delivery. The aim is to improve early detection, prevention and management of this complex problem. The results seek to contribute to more effective maternal care, detecting statistically significant associations between the variables analyzed and extreme maternal morbidity. Thus, it is expected that this study will have a positive impact on maternal health care in the hospital context of Iquitos.